LncRNA CTBP1-DT-encoded microprotein DDUP sustains DNA damage response signalling to trigger dual DNA repair mechanisms. Issue 14 (18th July 2022) - Yu, Ruyuan; Hu, Yameng; Zhang, Shuxia; Li, Xincheng; Tang, Miaoling; Yang, Meisongzhu; Wu, Xingui; Li, Ziwen; Liao, Xinyi; Xu, Yingru; Li, Man; Chen, Suwen; et al.
Abstract: Sustaining DNA damage response (DDR) signalling via retention of DDR factors at damaged sites is important for transmitting damage-sensing and repair signals. Herein, we found that DNA damage provoked the association of ribosomes with IRES region in lncRNA CTBP1-DT, which overcame the negative effect of upstream open reading frames (uORFs), and elicited the novel microprotein DNA damage-upregulated protein (DDUP) translation via a cap-independent translation mechanism. Activated ATR kinase-mediated phosphorylation of DDUP induced a drastic 'dense-to-loose' conformational change, which sustained the RAD18/RAD51C and RAD18/PCNA complex at damaged sites and initiated RAD51C-mediated homologous recombination and PCNA-mediated post-replication repair mechanisms. Importantly, treatment with ATR inhibitor abolished the effect of DDUP on chromatin retention of RAD51C and PCNA, thereby leading to hypersensitivity of cancer cells to DNA-damaging chemotherapeutics. Taken together, our results uncover a plausible mechanism underlying the DDR sustaining and might represent an attractive therapeutic strategy in improvement of DNA damage-based anticancer therapies.